How the Indonesia Stock Exchange Reacts to Information: A Speed of Adjustment Coeficients Study - Peranginangin, Yessy (The Indonesian Capital Market Review, 2009)
This study applies the ARMA model to estimate the speed of adjustment coeficients, as suggested by Theobal and Yallup (2004), in the IDX. There is not suficient evidence to conclude that the IDX overreacts to information. However, the indings suggest that the market either underreacts or fully adjusts to information. The IDX displays signiicant underreactions at weeky intervals that occur after the full adjustment. Investors' reaction is not sensitive to the size and liquidity of the indices. Size alone could not provide suficient explanation for the different adjustment pattern across sector indices.